Layanan Bimbingan dan Konseling yang Tidak Netral: Memahami Bentuk-Bentuk Mikroagresi Gender di Sekolah - Andi Wahyu Irawan; Bakhrudin All Habsy; Sedem Nunyuia Amedome (Pamomong: Journal of Islamic Educational Counseling, 2025)
Gender microaggressions within counseling services are frequently challenging to detect due to their subtle or indirect nature, often remaining unnoticed by both counselors and clients. Despite their seemingly minor nature, these microaggressions contribute to a non-neutral therapeutic environment, adversely impacting the comfort and psychological well-being of individuals, especially within the inherent power asymmetries between counselors and students. This study employs a case study methodology to explore the various manifestations of gender microaggressions in high school guidance and counseling settings. Data were gathered via in-depth interviews and observations involving two counselors and six students. Analytical procedures were guided by microaggression theory, categorizing behaviors into microinsults, Microassaults, and microinvalidations. The results reveal that gender microaggressions are expressed through stereotypical gender roles, neglect of students' emotional experiences, and the use of gender-biased language. This research significantly advances the discourse on gender awareness in counseling practices and emphasizes the need for gender-sensitive training among counseling professionals to foster a more inclusive environment conducive to students’ psychological well-being.